Identifikasi Permasalahan Siswa pada Aspek Masa Depan melalui AUM Umum di SMPN 4 Binjai - Cinta Roulina Sigalingging; Widia Abisah Br Ginting; Katrina Olivia; Devi Fifi Tarigan; Joy Triyola Situmeang; Vika Febrianti (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The research conducted aims to identify the problems faced by SMPN 4 Binjai students in the aspect of the future. The research method used is quantitative with a descriptive approach to provide a clear picture of the existing problems. The results obtained through this study show that students at SMPN 4 Binjai face some difficulties when planning their lives in the future. Therefore, schools need to collaborate with teachers especially guidance and counseling teachers as well as with parents to improve guidance and counseling services to help students overcome anxiety and difficulties when planning for the future.